THE IMPACT OF FARMING SYSTEMS IN THE DYNAMICS OF INDICATORS OF SOIL FERTILITY IN AGROFITOSENOSE SUGAR BEET - Танчик, С. П.; Сальніков, С. М. (Scientific Progress & Innovations, 2014)
The effect of cropping systems on the main indicators of soil fertility and yield of sugar beet has been examined. The statistical and mathematical analysis of the obtained data, and showed a high correlation between soil reaction and the total content of humus, during the growing season in agrophitocenosises sugar beet. It is established that the application of environmental and biological farming systems in which envisaged the use of organic fertilizers and by-products, a positive effect on the reaction of the soil solution, thereby increasing soil fertility indicators.